Hijacking nature—new approaches to unravel enzyme mechanisms and engineer improved biocatalysts. (12th March 2013) - Campeotto, Ivan; Acevedo‐Rocha, Carlos G
Abstract : The second EMBO conference on 'Catalytic Mechanisms by Biological Systems' took place in Groningen, the Netherlands, in October 2012. Structural, molecular and computational biologists, as well as chemists, biophysicists and engineers discussed technologies to improve our mechanistic understanding of enzymes, as well as the design of robust biocatalysts. Abstract : The second EMBO conference on 'Catalytic Mechanisms by Biological Systems' took place in October 2012 and covered technologies to improve our mechanistic understanding of enzymes, as well as the design of robust biocatalysts.